(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
This paper describes an intervention plan designed and implemented in the classroom for a student with special needs of educational support, that has a moderate intellectual disability, with learning difficulties in mathematics. This plan was carried out in a rural school of Castilla La Mancha, by a special education teacher, who has collaborated with the tutor, the counselor, and a faculty of the School of Education at the University of Castilla La Mancha. The intervention plan has involved identifying student’s level of development of logical and numerical thinking, and learning with manipulatives. The result has been positive for both the student and teaching staff. The student has improved his number skills and has acquired the sense of the numbers 1 and 2, a barrier difficult to overcame for him.